Differences in the efficiency between the grab and track starts for both genders in Greek young swimmers - Thanopoulos, V.; Rozi, G.; Okicic, T.; Dopsaj, M.; Jorgic, B.; Madic, D.; Velickovic, S.; Milanovic, Z.; Spanou, F.; Batis, E. (Journal of Human Kinetics, 2012)
The aim of this study was to determine the differences in the kinematic parameters between the grab and track starts and the differences in these two starts between genders. A total of 27 swimmers at the competitive level participated in the study, 13 boys (mean ± SD: age 15.8 ± 0.8 years, body mass 67.7 ± 7.7 kg and body height 178.6 ± 5.7 cm) and 14 girls (mean ± SD: age 16 ± 0.8 years, body mass 59.2 ± 6.6 kg and body height 166.2 ± 6.7 cm). Each swimmer performed three attempts for both start techniques. The best attempt of the grab start and the track start was taken for further analysis. The following kinematic parameters were analysed: flight distance, flight time, flight velocity, entry angle and reaction time. The males had greater numeric values for the results in all kinematic parameters for the grab start compared with the track start, except for flight velocity and entry angle (flight time 0.42 vs. 0.41 s, flight distance 3.21 vs. 3.14 m, flight velocity 7.76 vs. 7.83 m/s, entry angle 44.22 vs. 43.85 degrees and reaction time 0.86 vs. 0.81 s). The females also had greater numeric values for the results in all kinematic parameters for the grab start compared with the track start, except for flight time (flight time 0.38 vs. 0.38 s, flight distance 2.82 vs. 2.73 m, flight velocity 7.47 vs. 7.31 m/s, entry angle 45.18 vs. 44.79 degrees and reaction time 0.88 vs. 0.82 s). These results indicate that the males had significantly better results for flight time and flight distance compared with the females for the grab start (flight time 0.42 vs. 0.38 s, flight distance 3.21 vs. 2.82 m). In the case of the track start, the males had significantly better results for flight distance (3.14 vs. 2.73 m). Exploring the characteristics of the two starts did not lead to any significant kinematic differences. Therefore, a conclusion that demonstrates the superiority of one of the techniques cannot be reached. The coach, together with each swimmer individually, should devote some time to decide after some tests what type of start is better for the body type and general qualifications of the swimmer.